2020
DOI: 10.24252/eternal.v62.2020.a5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Junior High School Students’ Errors in Using English Past Tense: A Look From Technological and Sociological Foundations

Abstract: This study aims at investigating junior high school students’ errors in using English past tense in their English compositions. The subjects of this study were 8th-grade students in a junior high school in North Bali. This study employed descriptive qualitative research which describes the error that was produced by EFL learners. There were four steps in collecting the data namely, asking the students to watch a video, telling them to write recount text through guided writing, collecting the learners' writing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Due to the fact that a copula is not required, predication may be expressed using a two-word or one-word nonverbal utterance (Adnyani et al, 2018). Various studies have reported the absence of BE in a student's English production (Burhansyah, 2019;Fauziati, 2011;Fauziati & Maftuhin, 2016;Gayo & Widodo, 2018;Iman, 2020;Kusumawardani & Adnyani, 2020;Mandarani, 2020;P. Sari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the fact that a copula is not required, predication may be expressed using a two-word or one-word nonverbal utterance (Adnyani et al, 2018). Various studies have reported the absence of BE in a student's English production (Burhansyah, 2019;Fauziati, 2011;Fauziati & Maftuhin, 2016;Gayo & Widodo, 2018;Iman, 2020;Kusumawardani & Adnyani, 2020;Mandarani, 2020;P. Sari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…So far, research has concentrated on error analysis and interlanguages (Aini et al, 2020;Burhansyah, 2019;Fauziati, 2011Fauziati, , 2017Fauziati & Maftuhin, 2016;Fauziati & Nugroho, 2019;Gayo & Widodo, 2018;Gumilar et al, 2018;Kusumawardani & Adnyani, 2020;Maheswari et al, 2020;Mandarani, 2020;Pratiwi et al, 2020;Puspita, 2019;E. Sari, 2016;P. Sari et al, 2020;Suwastini et al, 2020;Tiarina, 2017).…”
Section: Introductionmentioning
confidence: 99%